2022
DOI: 10.1371/journal.pone.0272232
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-treatment prognostic nutritional index and the haemoglobin, albumin, lymphocyte and platelet (HALP) score on endometrial cancer survival: A prospective database analysis

Abstract: Purpose The Onodera’s prognostic nutritional index (PNI) and the haemoglobin, albumin, lymphocyte and platelet (HALP) score are immune-nutritional indices that correlate with survival outcomes in several adult solid malignancies. The aim of this study was to investigate whether PNI and HALP are associated with survival outcomes in endometrial cancer. Patients and methods Women undergoing management for endometrial cancer were recruited to a single centre prospective cohort study. Pre-treatment PNI and HALP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
(87 reference statements)
1
16
0
Order By: Relevance
“…It is worth noting that several papers only looked at patients of single sex. For example, papers on breast, endometrial, and cervical cancer only considered female patients, while papers on prostate cancer and one paper on esophageal cancer exclusively male populations [48,[61][62][63][64][65][66]. Two papers on pharyngeal cancer had primarily male populations [49,67].…”
Section: Halp and Sexmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that several papers only looked at patients of single sex. For example, papers on breast, endometrial, and cervical cancer only considered female patients, while papers on prostate cancer and one paper on esophageal cancer exclusively male populations [48,[61][62][63][64][65][66]. Two papers on pharyngeal cancer had primarily male populations [49,67].…”
Section: Halp and Sexmentioning
confidence: 99%
“…Furthermore, HALP scores have been used in endometrial cancer patients. In a prospective study by Njoku et al, on 439 endometrial cancer patients, HALP was specifically associated with FIGO staging, histology, disease grade, LVSI, and deep myometrial invasion [ 63 ]. However, HALP scores were not shown to be associated with overall, cancer-specific or recurrence-free survival, which this study concluded could be due to unaccounted confounders affecting HALP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) Several in ammatory biomarkers and nutritional indicators, such as the neutrophil-albumin ratio (NAR) and the combined index of hemoglobin, albumin, lymphocyte, and platelet(HALP), correlate with prognosis in many cancers. (2,(17)(18)(19) However, the pred ictive usefulness of these biomarkers for mPC is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The nutrition parameters, such as serum albumin and hemoglobin levels, and inflammation parameters, such as lymphocyte and platelet counts, have been reported to have substantial roles in OSCC prognostication. [10][11][12] Recently, the hemoglobin-albumin-lymphocyte-platelet (HALP) score integrates the aforementioned parameters and has been demonstrated to be a prognostic biomarker in cancers of the pancreas, 13 bladder, 14 prostate, 15 endometrium, 16 breast, 17 and cervix. 18 Thus, the adoption of a relatively high-accuracy and convenient preoperative laboratory index in prognostic stratifications of OSCC might contribute to a better prognosis with optimal adjuvant therapies.…”
mentioning
confidence: 99%